Experimental and Clinical Methods for Assessing the Primary Stability of Dental Implants: Current Capabilities and Future Prospects (Literature Review) - Ashrafov, Davud Sergey; Mehmani, Ilham Gasanaga; Gurskaya, Narmina Azad (Actual Dentistry, 2026)
Abstract. The success of implant-supported prosthetic treatment largely depends on primary stability, a critical determinant of successful osseointegration. Evaluating implant stability together with the condition of the surrounding bone enables clinicians to anticipate the integration process and detect potential complications during healing and bone remodeling. Modern clinical approaches include instrumental and imaging diagnostic techniques, such as resonance frequency analysis (RFA) and Periotest measurements; however, their objectivity and applicability in routine practice remain a matter of ongoing debate. In addition to established methods, experimental and less widely used hardware-based approaches are actively being investigated, allowing quantitative evaluation of implant–bone interactions and measurement of stability parameters in physical units. Among these technologies, ultrasound analysis is considered promising, as it enables comparison with histomorphological data on osseointegration and provides objective quantitative measures of primary implant stability. Purpose: to evaluate current methods for determining the primary stability of dental implants and their correlation with objective indicators of osseointegration, specifically bone–implant contact (BIC), as well as to identify the potential for their clinical application. Materials and Methods. For this review, a targeted search of scientific publications was conducted in three recognized international databases: PubMed, Scopus, and Web of Science, covering recent years. The search employed a combination of keywords related to the topic, including dental implants, primary stability, osseointegration, and implant stability assessment. Articles were selected based on strict criteria for relevance to the review topic and scientific merit. A total of 21 sources were included in the final analysis, comprising both review articles and original research. Each publication underwent a qualitative assessment, focusing on relevance, methodological rigor, and the novelty of the reported findings. This approach provided a comprehensive and up-to-date understanding of current methods for evaluating the primary stability of dental implants. Results. Analysis of the literature indicates that resonance frequency analysis (RFA) and Periotest can be used to assess implant stability at various stages of osseointegration, but their precision is limited, and they do not fully capture either the mechanical or biological aspects of integration. Experimental methods, including ultrasound diagnostics, electromechanical impedance, and laser testing, provide more objective results expressed in physical units and demonstrate correlation with bone–implant contact (BIC), making them promising tools for clinical and research evaluation of both primary and secondary implant stability.